Acute inflammatory response to prolonged sculling in competitive male rowers - Jürimäe, J.; Tillmann, V.; Purge, P.; Jürimäe, T. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: This study examined the effects of a prolonged low-intensity single scull rowing exercise on a complex of 12 different inflammatory cytokines in rowers.